2017
DOI: 10.1615/intjmedmushrooms.2017024487
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Reference Genes and Analysis of Heat Shock Protein Gene Expression in Lingzhi or Reishi Medicinal Mushroom, Ganoderma lucidum, after Exposure to Heat Stress

Abstract: Ganoderma lucidum has been considered an emerging model species for studying how environmental factors regulate the growth, development, and secondary metabolism of Basidiomycetes. Heat stress, which is one of the most important environmental abiotic stresses, seriously affects the growth, development, and yield of microorganisms. Understanding the response to heat stress has gradually become a hotspot in microorganism research. But suitable reference genes for expression analysis under heat stress have not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In later studies, the expression levels of the housekeeping genes were found unstable under abiotic and biotic stress [26,30], suggesting the importance of reliable reference genes for qRT-PCR analysis. The stability of reference genes was evaluated under different development stages, nutrient conditions, and abiotic stresses in G. lucidum , V. volvacea, L. edodes , and Pleurotus ostreatus [21,24,26,31]. In the present study, we focused on the reference genes for shiitake mushroom in the early stage of the hot-air drying process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In later studies, the expression levels of the housekeeping genes were found unstable under abiotic and biotic stress [26,30], suggesting the importance of reliable reference genes for qRT-PCR analysis. The stability of reference genes was evaluated under different development stages, nutrient conditions, and abiotic stresses in G. lucidum , V. volvacea, L. edodes , and Pleurotus ostreatus [21,24,26,31]. In the present study, we focused on the reference genes for shiitake mushroom in the early stage of the hot-air drying process.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been performed on the selection and evaluation of stable reference genes under different conditions, such as different development stages and nutrient conditions as well as abiotic stresses in Morchella [19], Ganoderma lucidum [20,21,22], Volvariella volvacea [23,24], and L. edodes [25,26]. Nevertheless, the information about the reference genes used for qRT-PCR normalization of the hot-air-dried L. deodes is rather limited.…”
Section: Introductionmentioning
confidence: 99%
“…The hyphae cultured in CYM for 7 days were used to extract RNA, and the extraction method of the total RNA has been described previously [25]. We used quantitative real‐time PCR (qRT‐PCR) to detect messenger RNA expression of the HMX1 gene and other testing genes in the WT, Sicontrol, and HMX1 ‐silenced strains, as previously described [26]. We used the 18S rRNA housekeeping gene to normalize the expression of other target genes, and the primers used are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%